ETIOLOGY, CLASSIFICATION, AND MULTIDISCIPLINARY MANAGEMENT OF HYPERTROPHIC GINGIVITIS: A CLINICAL REVIEW (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Hypertrophic gingivitis (HG) is a proliferative periodontal disorder characterized by the enlargement of the gingival tissues. This condition poses significant challenges to oral hygiene maintenance and aesthetic harmony. This article reviews the multifaceted etiology of HG, distinguishing between its edematous and fibrous clinical manifestations. We evaluate current diagnostic protocols and therapeutic interventions, emphasizing the shift toward minimally invasive laser surgery and the necessity of managing underlying systemic triggers.